Football Championships and Jersey Sponsors' Stock Prices: An Empirical Investigation - Michael Hanke; Michael Kirchler (University of Innsbruck, Department of Public Finance, 2010)
Corporate sports sponsorship is an important part of many companies' corporate communication strategy. We take the example of major football tournaments to show that sponsorship indeed affects the sponsor's (stock) market value. We find a statistically significant impact of football results (at an individual game level) of the seven most important football nations at European and World Championships on the stock prices of jersey sponsors. In general, the more important a match and the less expected its result, the higher its impact. In addition, we find a form of mere exposure-effect which contradicts the efficient markets hypothesis.
Keywords: G14; 330; Sports sponsorship; Advertising; Stock market efficiency; Fußballsport; Sponsoring; Börsenkurs; Effizienzmarktthese; Europa